2000
DOI: 10.1046/j.1365-2583.2000.00156.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of the ribosomal protein CcP0 of the medfly Ceratitis capitata

Abstract: The gene of the ribosomal protein CcP0, the third member of the ribosomal P-protein family of the medfly Ceratitis capitata, was identified by genomic and cDNA sequence analysis. It codes for a polypeptide of 317 amino acids and its predicted amino acid sequence shows great similarity to the P0 proteins of other eukaryotic organisms. The CcP0 gene was expressed in Escherichia coli and the 34-kDa recombinant protein was identical to the P0 protein of purified medfly ribosomes. Both proteins reacted positively w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
0
4
0
3
Order By: Relevance
“…[15,27] Some studies reported that the expression of CHS1/A was much higher than that of CHS2/B in a variety of insect species. [16,28] The CHSs activity we obtained in this study may therefore represent CHSA activity. After evaluating MysCHSA gene expression during different developmental stages and tissues of M. separata using qRT-PCR, we found that higher expression of MysCHSA was detected in mature larvae and the pupal period, which likely reflects the necessity for higher chitin content in the exoskeleton (Supporting Information, Figure 3A).…”
Section: Discussionmentioning
confidence: 90%
“…[15,27] Some studies reported that the expression of CHS1/A was much higher than that of CHS2/B in a variety of insect species. [16,28] The CHSs activity we obtained in this study may therefore represent CHSA activity. After evaluating MysCHSA gene expression during different developmental stages and tissues of M. separata using qRT-PCR, we found that higher expression of MysCHSA was detected in mature larvae and the pupal period, which likely reflects the necessity for higher chitin content in the exoskeleton (Supporting Information, Figure 3A).…”
Section: Discussionmentioning
confidence: 90%
“…In the yeast Saccharomyces cerevisiae four different P-proteins have been found; two of them belonging to the P1 family (YP1α and YP1β) and two to the P2 family (YP2α and YP2β), based on amino acid sequence comparisons to their mammalian counterparts (for a review see 10). In the medfly Ceratitis capitata, biochemical analysis of total ribosomes revealed that the ribosomal P-protein family consists of two acidic proteins, CcP1 and CcP2, of 17 and 15 kDa, respectively, and of one 34 kDa basic protein, CcP0 (11,12). The genes encoding these proteins have been recently cloned and identified by genomic and *To whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Παράλληλα ένας σηµαντικός αριθµός γονιδίων της C. capitata έχει κλωνοποιηθεί και χαρακτηρισθεί (Tolias et al, 1990;Konsolaki et al, 1990;Rina and Savakis, 1991;Haymer et al, 1990;Scott et al, 1993;Zwiebel et al, 1995;Banks et al, 1995;Vlachou et al, 1997;Gomulski et al, 1998;Thymianou et al, 1998;Papadimitriou et al, 1998;Saccone et al, 1998;Verras et al, 1999;Gagou et al, 1999;Gagou et al, 2000;Christofides et al, 2000;Brogna et al, 2001). Τα περισσότερα από αυτά τα γονίδια έχουν χαρτογραφηθεί µε in situ υβριδοποίηση στα πολυταινικά χρωµοσώµατα και σε συνδυασµό µε αρκετούς άλλους "ανώνυµους" κλώνους έχουν αποτελέσει µοριακούς δείκτες για περισσότερες από 100 θέσεις στα πολυταινικά χρωµοσώµατα (Zacharopoulou et al, 1992;Kρητικού, 1997;Gariou-Papalexiou et al, 2002).…”
Section: εισαγωγήunclassified